2006
DOI: 10.1007/s10661-006-9460-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Storage and Filtration Protocols for Alpine/Subalpine Lake Water Quality Samples

Abstract: Many government agencies and other organizations sample natural alpine and subalpine surface waters using varying protocols for sample storage and filtration. Simplification of protocols would be beneficial if it could be shown that sample quality is unaffected. In this study, samples collected from low ionic strength waters in alpine and subalpine lake inlets and outlets in the western United States were used to evaluate (1) effects of refrigerated storage time on the chemistry of unfiltered samples, and (2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…There was no effect of 0.45 µm filtration on A T of water samples from across a salinity spectrum. Other studies have also found no effects of filtration on the A T of alpine freshwater, pond water, and seawater 6 , 9 , 11 , 21 , 22 . Importantly there were no changes in the A T of filtered samples stored in polypropylene vials for at least 6 months, with the exception of groundwater in two of three experiments, demonstrating the enduring effectiveness of filtration.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…There was no effect of 0.45 µm filtration on A T of water samples from across a salinity spectrum. Other studies have also found no effects of filtration on the A T of alpine freshwater, pond water, and seawater 6 , 9 , 11 , 21 , 22 . Importantly there were no changes in the A T of filtered samples stored in polypropylene vials for at least 6 months, with the exception of groundwater in two of three experiments, demonstrating the enduring effectiveness of filtration.…”
Section: Discussionmentioning
confidence: 87%
“…The drawbacks of HgCl 2 have driven the search for low-cost, safer, and more environmentally benign alternatives 18 . Filtration does not affect the A T of alpine freshwater 9 , pond water 11 , or seawater 21 23 . Filtration is as or more effective than HgCl 2 in preserving stable isotope compositions ( δ 13 C) in dissolved inorganic carbon 24 , 25 .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Immediately prior to use, all individual soil samples were sieved to 4 mm to remove plant materials, large stones, and earthworms followed by thorough mixing. Additionally, upstream and downstream water samples (n = 4) draining the BIFoR woodlands were sampled according to standard water sampling procedure 41,42 . Water analyzed for Nr included filtered and unfiltered samples since measurement using FIA required samples to be free of suspension.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, upstream and downstream water samples (n = 4) draining the BIFoR woodlands were sampled according to standard water sampling procedure. 41 , 42 Water analyzed for Nr included filtered and unfiltered samples since measurement using FIA required samples to be free of suspension. Pictures of sample location site are enclosed in Figure SI2.…”
Section: Methodsmentioning
confidence: 99%